2021
DOI: 10.1167/iovs.62.10.34
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreflective Foci, Optical Coherence Tomography Progression Indicators in Age-Related Macular Degeneration, Include Transdifferentiated Retinal Pigment Epithelium

Abstract: Purpose By optical coherence tomography (OCT) imaging, hyperreflective foci (HRF) indicate progression risk for advanced age-related macular degeneration (AMD) and are in part attributable to ectopic retinal pigment epithelium (RPE). We hypothesized that ectopic RPE are molecularly distinct from in-layer cells and that their cross-retinal course follows Müller glia. Methods In clinical OCT (61 eyes, 44 patients with AMD, 79.4 ± 7.7 years; 29 female; follow-up = 4.7 ± 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 84 publications
(119 reference statements)
4
53
0
Order By: Relevance
“…1 ) as well as in CNS disease such as multiple sclerosis (MS) an increase in the number of HRS has been documented [ 24 , 29 31 ]. Histologic evidence from human donor eyes with AMD and acquired vitelliform lesions demonstrated that HRS visualized on SD-OCT may originate from both anteriorly migrated retinal pigment epithelium cells and lipid-filled cells (thought to correspond to activated microglia) [ 32 34 ]. In patients with diabetic macular oedema, a positive correlation between the number of HRS and aqueous humour concentration of soluble CD14 (a cytokine associated with immune response, expressed in microglia, monocytes and macrophages) was reported [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 ) as well as in CNS disease such as multiple sclerosis (MS) an increase in the number of HRS has been documented [ 24 , 29 31 ]. Histologic evidence from human donor eyes with AMD and acquired vitelliform lesions demonstrated that HRS visualized on SD-OCT may originate from both anteriorly migrated retinal pigment epithelium cells and lipid-filled cells (thought to correspond to activated microglia) [ 32 34 ]. In patients with diabetic macular oedema, a positive correlation between the number of HRS and aqueous humour concentration of soluble CD14 (a cytokine associated with immune response, expressed in microglia, monocytes and macrophages) was reported [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This contrasted with our observation of a HRF which remained static during follow-up. In the literature, migration of a HRF toward the inner retina was previously reported (23) as well as stability over several years (19) but not centrifugal migration. Hence, taken collectively, these data suggests that subretinal hyperreflective spots and HRFs may behave differentially.…”
Section: Discussionmentioning
confidence: 91%
“…Along margins of atrophy, duplication of the RPE layer has also been described ( 16 ), which may account for short wavelength hyperautofluorescence seen clinically ( 17 ). Whether this pigment mottling corresponds to detached RPE cells ( 14 , 15 ) transdifferentiated RPE cells ( 18 , 19 ) or macrophages that have phagocytozed RPE cells ( 20 , 21 ) is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Intraretinal migration of injured RPE cells is well known in AMD, where they appear as hyper-reflective foci in optical coherence tomography (OCT) studies. [31,32] Under these conditions, RPE cells can transdifferentiate into mesenchymal phenotypes, [32,33] including macrophage-like cells. [34] RPE transdifferentiated cells are key players in the development of human and experimental proliferative vitreoretinopathy membranes.…”
Section: Main Findingsmentioning
confidence: 99%